ANALISIS ARAH KIBLAT DI ATAS KENDARAAN PERSPEKTIF ILMU FIKIH - Ulfawati, Ulfawati; Syarif, Muh.Rasywan (Universitas Islam Negeri Alauddin Makassar, 2025)
Determining the direction of the Qibla is one of the valid requirements for performing prayers, especially for Muslims who perform them under normal conditions. However, under certain conditions, such as when traveling by vehicle—whether on land, sea, or air—the ability to face the Qibla correctly often encounters obstacles. This study raises two research questions: how to determine the direction of the Qibla on a vehicle from a fiqh perspective and what inhibiting factors exist in determining the direction of the Qibla on a vehicle. The research method used is qualitative with library research. Data were obtained from primary sources such as the Qur'an and hadith, as well as secondary data sources such as books, journals, and scientific articles. The approaches used are the sharia approach and the philosophical approach. The data collection method used is collecting, reading, and analyzing various written sources related to the research topic. The results of the study show that the method used in determining the direction of the Qibla on a vehicle uses 2 methods, namely, a method with the help of nature such as sunrise and sunset, and using the shadow of an object while the second method, using modern tools such as Global Positioning System (GPS), compass, google earth. Inhibiting factors in determining the direction of the Qibla such as the lack of certainty of accuracy in the precision of the Qibla direction, dependence on technological tools without sharia references, misinterpretation of lay people, not in accordance with the classical hisab-rukyat tradition, signal interference and dependence on technology, and so on. The implications of this study are expected to be a treasure of knowledge and continue to maintain our obligations as Muslims, namely the five daily prayers wherever we are, especially during long journeys.